Study on properties of tapioca resin polymer - Jamiluddin, J.; Siregar, J. P.; Sulaiman, A. H.; A. Jalal, K. A.; Tezara, C. (Universiti Malaysia Pahang, 2016)
Environmental, global warming, renewability, recyclability, and biodegradability issues have encouraged scientists and engineers to partially substitute petrochemical-based polymers with green polymers such as natural fibre polymer composites. A major drawback in the development of natural fiber polymer composites is the incompatibility between the matrix and fibre processing temperature, given the high temperature of the matrix based on petroleum and the low degradation temperature for natural fibre. The creation of poly lactic acid as a “green matrix” provides an alternative and a solution for the development of natural fiber polymer composites. In this work, the physical, thermal and mechanical properties of PLA tapioca resin biopolymer derived from industrial grade tapioca were reported in order to determine the optimum processing temperature. A drying process, injection moulding and hot press process are involved in sample preparation. A density test, hardness test, thermogravimetric analysis, and differential scanning calorimetry have been conducted. Afterwards, a tensile test was performed with samples at five different injection temperatures of 160°C, 165°C, 170°C, 175°C and 180°C in order to determine the optimum processing temperature. The sample at 165°C shows the highest result of ultimate tensile strength with 14.904 MPa, and 320.564 MPa for the elastic modulus result. As a conclusion, 165°C was finalized as the optimum processing temperature of PLA tapioca resin biopolymer for future application in the research and development of natural fibre reinforced tapioca resin biopolymer composite.